Needle-tissue interaction force study during simulated regional anaesthesia. (May 2020) - Zhang, Shengli; Graeme,; George,; Qiao, Panpan; Huang, Zhihong; Xia, Chunming
Abstract: Needle insertion usually performed with the aid of an Ultrasound (US) image in the regional anaesthesia. Getting the position of the needle tip from US requires the technical expertise and skilled anaesthetist. To detect where the needle tip is around the nerve during the needle insertion, a modified block needle attached with a force sensor is used to feedback the amount of counter force from the needle tip. This paper is to investigate whether needle force under ultrasound guidance can guide anaesthesiologists in identifying the relative position of the needle tip and nerve The goal of our research was to use the visual needle tip force to guide the anaesthetist to detect the relative positions between the needle tip and nerve.